Implementation of Inclusive Character Education for Children with Special Needs in Regular Schools - Amka Amka (Madrosatuna: Journal of Islamic Elementary School, 2017)
This paper aims to examine the implementation of inclusive character education for Children with pecial Needs (ABK) in regular schools. In learning, ABK children have different characters and modalities with normal learners. To that end, approaches, methods, techniques, and learning tactics need to be tailored to the learning needs to be meaningfully appropriate to the students' ABK. Permendiknas Number 70 of 2009 on Inclusive Education aims to provide the widest opportunity to all learners who have physical, emotional, mental and social abnormalities or have the potential of intelligence and / or special talents to obtain quality education according to their needs and abilities. Inclusive character education can be realized by actualizing the value of the wombs characterized by child-friendly learning. Implementation of inclusive character education in regular schools is characterized by child-friendly learning, empathy, learner-centered learning, and pursuit according to the learning needs of learners. Schools need to assess the needs of learners, complement the ABK-based sarpras and accessible child-friendly schools. Thus the curriculum, learning, interaction, and assessment of learning will be tailored to the needs of learners with special needs. This is the true value of the character, the learning that respects the learners.